Cosmic rays return to Florence - Spillantini, Piero (Il Colle di Galileo, 2025)
I wanted to tell my story as a scientist, made up also of chance meetings and coincidences, which has led to the return of cosmic ray research to Florence in recent decades. This journey encompasses the combination of personal facts, passions, shared ideas and projects, as well as well-known geopolitical events that have contributed to the development of astro-particle science in the place where the first pioneers of this field worked nearly a century ago.